입원환자의 낙상 위험 예측 요인 - 김은경; 이재창; 엄미란; Kim, Eun-Kyung; Lee, Jae-Chang; Eom, Mi-Ran (Journal of Korean Academy of Nursing, 2008)
Purpose: The purpose of this study was to identify the risk factors for falls and to suggest data for developing a program for preventing falls. Methods: This was a case-control study in five university hospitals and a general hospital. In total, 216 patients over the age of 18 yr admitted from January 1 to December 31, 2007 participated. One hundred eight patients with experience of falling were matched by gender, age level, diagnosis, and length of stay with 108 patents with no experience of falling admitted on the same unit. A quality assurance coordinator nurse in each hospital examined 35 fall risk factors developed by researchers. Results: In acute hospitals, history of falls, orientation ability, dizziness or vertigo, general weakness, urination problems, transfer/mobility difficulty, walking dependency, impatience, benzodiazepines, diuretics, and vasodilators showed significance on adjusted-odds ratios for fall. Logistic regression analysis was performed to elucidate the factors that influence falls. The probability of falls was increased by dizziness/vertigo, general weakness, and impatience/agitation. Conclusion: This finding can be used as a useful resource in developing nursing intervention programs to predict and prevent the falls of inpatients.